Application of edible nanolaminate coatings with antimicrobial extract of Flourensia cernua to extend the shelf-life of tomato (Solanum lycopersicum L.) fruit - Salas-Méndez, Esperanza de Jesús (2019)
Supplementarymaterialrelatedtothisarticlecanbefound,inthe online version, at doi:https://doi.org/10.1016/j.postharvbio.2018.12. 008.